2021
DOI: 10.1101/2021.05.25.445163
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparative transcriptome analysis of noble crayfish and marbled crayfish immune response to Aphanomyces astaci challenges

Abstract: Introduction of invasive North American crayfish species and their pathogen Aphanomyces astaci has significantly contributed to the decline of European freshwater crayfish populations. In this study, noble crayfish, a susceptible native European species, and marbled crayfish, an invasive disease-resistant species, were challenged with haplogroup A (low virulence) and haplogroup B (high virulence) strain of A. astaci. Hepatopancreatic tissue was isolated 3 and 21 days post-challenge. Our results revealed stron… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 152 publications
(195 reference statements)
2
11
0
Order By: Relevance
“…The controlled infection experiment by Francesconi et al provided additional evidence of how drastically strains of A. astaci differ in their virulence. This study confirmed the adaptation of one specific A. astaci haplogroup to their novel European hosts, supposedly due to ongoing coevolution (Jussila et al, 2021) as confirmed by transcriptomic data analyses (Boštjančić et al, 2021). Furthermore, Francesconi et al experimentally showed that invasive marbled crayfish are remarkably resistant against the crayfish plague disease and could potentially be latently infected, acting as carriers of virulent A. astaci strains.…”
Section: Crayfish Plague Managementsupporting
confidence: 79%
“…The controlled infection experiment by Francesconi et al provided additional evidence of how drastically strains of A. astaci differ in their virulence. This study confirmed the adaptation of one specific A. astaci haplogroup to their novel European hosts, supposedly due to ongoing coevolution (Jussila et al, 2021) as confirmed by transcriptomic data analyses (Boštjančić et al, 2021). Furthermore, Francesconi et al experimentally showed that invasive marbled crayfish are remarkably resistant against the crayfish plague disease and could potentially be latently infected, acting as carriers of virulent A. astaci strains.…”
Section: Crayfish Plague Managementsupporting
confidence: 79%
“…From the pooled Trinity de novo transcriptome assembly we obtained 670,741 transcripts for the noble crayfish (44,062 ORFs) and 11,333,173 (46,953 ORFs) transcripts for the marbled crayfish . In the post-assembly processing, after filtering fragmented transcripts 168,172 (44,062 ORFs) and 348,751 (46,953 ORFs) transcripts remained for the noble crayfish [ 10 ] and the marbled crayfish , respectively [ 11 ]. After redundancy reduction with CD-HIT-EST 109,608 genes and 254,336 genes remained for the noble crayfish and the marbled crayfish , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…BUSCO analysis of the final assembly revealed a high level of completeness for both assemblies, 93.30% for the noble crayfish and 93.98% for the marbled crayfish arthropoda_odb10 database of orthologs (n = 1013). Comparative analysis of the BUSCO scores among available freshwater crayfish transcriptomes placed the noble crayfish and the marbled crayfish transcriptome assemblies as the most complete freshwater crayfish transcriptome assemblies to date [ 12 ]. Length distribution of assembled transcripts varied from 401 to 32,629 in the noble crayfish and 401 to 32,816 in the marbled crayfish, with the highest number of transcripts falling in the category of 401–500 bp in length for both species [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations